Activation of non-canonical TGF-β1 signaling indicates an autoimmune mechanism for bone marrow fibrosis in primary myelofibrosis - Ciaffoni, Fiorella (Blood Cells Mol Dis, 2015)
Primary myelofibrosis (PMF) is characterized by megakaryocyte hyperplasia, dysplasia and death with progressive reticulin/collagen fibrosis in marrow and hematopoiesis in extramedullary sites. The mechanism of fibrosis was investigated by comparing TGF-β1 signaling of marrow and spleen of patients with PMF and of non-diseased individuals. Expression of 39 (23 up-regulated and 16 down-regulated) and 38 (8 up-regulated and 30 down-regulated) TGF-β1 signaling genes was altered in marrow and spleen of PMF patients, respectively. Abnormalities included genes of TGF-β1 signaling, cell cycling and abnormal in chronic myeloid leukemia (EVI1 and p21(CIP)) (both marrow and spleen) and Hedgehog (marrow only) and p53 (spleen only) signaling. Pathway analyses of these alterations predict increased osteoblast differentiation, ineffective hematopoiesis and fibrosis driven by non-canonical TGF-β1 signaling in marrow and increased proliferation and defective DNA repair in spleen. Since activation of non-canonical TGF-β1 signaling is associated with fibrosis in autoimmune diseases, the hypothesis that fibrosis in PMF results from an autoimmune process triggered by dead megakaryocytes was tested by determining that PMF patients expressed plasma levels of mitochondrial DNA and anti-mitochondrial antibodies greater than normal controls. These data identify autoimmunity as a possible cause of marrow fibrosis in PMF.